Polycythaemia Rubra Vera: A Case Report & Review of Literature - Haq, M Maksumul; Nasrin, Sahela; Taimur, Syed Dawood Md; Gomes, Hemanta I; Rahman, Mohammad Arifur (University Heart Journal, 2011)
We report a case of 73 year old woman with known risk factor (hypertension) for cerebrovascular disease who developed a TIA like symptom & vertigo with spontaneous clinical improvement. CT showed left cerebral infarct. Haematological test revealed PRV. Clinical improvement was associated with a reduction in haematocrit levels. Hydroxyurea appears to be the least leukemogenic myelosuppressive agent in long term prospective clinical PRV studies extending observation period of >10 years. Low dose aspirin will prevent the microvascular thrombotic complications of thrombocythaemia associated with PRV in remission after phlebotomy. Key words: Polycythaemia Rubra Vera(PRV); Thrombosis; Ischemic stroke DOI: 10.3329/uhj.v6i2.7259 University Heart Journal Vol. 6, No. 2, July 2010 pp.114-116